Temperature-Sensitive PNIPAM Hydrogels: A Solution for Workability Loss and Shrinkage in Cement Paste (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
Cement paste is a crucial component in construction, but it often faces significant challenges such as workability loss and shrinkage, which can impact the quality and durability of concrete structures. This article explores the innovative use of temperature-sensitive PNIPAM (poly (N-isopropylacrylamide)) hydrogels to address these issues. PNIPAM hydrogels are known for their thermo-responsive properties, transitioning between hydrophilic and hydrophobic states at a specific temperature known as the Lower Critical Solution Temperature (LCST). This phase transition allows PNIPAM hydrogels to modulate water content dynamically, enhancing the workability of cement paste and mitigating shrinkage. The study investigates the synthesis, functionalization, and integration of PNIPAM hydrogels into cement paste, highlighting their impact on workability through improved fluidity and reduced setting times, as well as their effectiveness in reducing plastic, drying, and autogenous shrinkage. Experimental results demonstrate that PNIPAM hydrogels significantly improve the consistency and stability of cement paste, offering a promising solution to common performance issues. The article discusses practical applications in construction, economic considerations, and environmental benefits, while also proposing directions for future research. By leveraging the thermo-responsive capabilities of PNIPAM hydrogels, this study presents a novel approach to enhancing cement paste performance, with implications for improved construction efficiency and durability.